What have been highly pointed in bread and sourdough researches: using bibliometric analysis as a powerful tool - Sokmen, Ozen; Gürçam, Özlem Sökmen; Dündar, Ayşe Neslihan; Sarıcaoğlu, Furkan Türker (International Society of Academicians, 2022)
In this study provided the opportunity to create a coherent general perspective towards research trends and basic studies in the literature, especially about “bread” and “sourdough”. The objective of this study is to analyze the evolution of trends in research topics in different countries and across the years (from 1989 to March 2021) in the literature on bread and sourdough by means of a term map analysis. In this regard, the present study was designed to reveal the hot topics. A total of 338 scientific papers were retrieved from the Web of Science (WOS) between 1989 and March 2021. VOSviewer software program was used to visualize these articles. 275 of these 338 articles consist of documents written in the field of “Food Science Technology”. The author with the most articles was Gobbetti M. It was found out that the most contributing publication to the field was the article entitled “Impact of sourdough on the texture of bread”. Italy stands out in studies compared to other countries, with the most published author is Italian. It was observed that studies on bread and yeast increased over the years with the advancement of technology and that different studies were carried out on bread and sourdough.
Keywords: Food Engineering; Gıda Mühendisliği